Protective Effects of Parental Education Against Youth Cigarette Smoking: Diminished Returns of Blacks and Hispanics - Assari S; Mistry R; Caldwell CH; Bazargan M (Dove Medical Press, 2020)
Shervin Assari,1 Ritesh Mistry,2 Cleopatra H Caldwell,2 Mohsen Bazargan1,3 1College of Medicine, Charles R Drew University of Medicine and Science, Los Angeles, CA 90059, USA; 2Department of Health Behavior and Health Education, University of Michigan School of Public Health, Ann Arbor, MI, 48109, USA; 3Department of Family Medicine, University of California, Los Angeles (UCLA), Los Angeles, CA, 90095, USACorrespondence: Shervin AssariDepartment of Family Medicine, Charles R. Drew University of Medicine and Science, 1731 E. 120th St., Los Angeles, CA 90059, USAEmail assari@umich.eduBackground: High parental educational attainment is protective against youth health risk behaviors such as tobacco use. According to the Marginalization-related Diminished Returns (MDRs) theory, however, higher parental education is less protective for marginalized groups relative to non-Hispanic Whites.Objective: To explore race/ethnic differences in the effects of parental educational attainment on cigarette smoking in a national sample of American adolescents.Methods: In a cross-sectional study, we used baseline data of 10,878 American youth who had participated in the Population Assessment of Tobacco and Health (PATH 2013). The independent variable was parental educational attainment. The dependent variables were lifetime cigarette smoking, current (past 30-day) cigarette moking, and daily cigarette smoking. Youth age, youth gender, and parental marital status were the covariates. Race/ethnicity was the moderating variable. Logistic regression model was used for data analysis.Results: Overall, a higher parental educational attainment was associated with a lower lifetime cigarette smoking, current (past 30-day) cigarette smoking, and daily cigarette smoking. Parental educational attainment showed significant interaction with race/ethnicity suggesting smaller protective effects of parental educational attainment on youth tobacco outcomes for Black and Hispanic than for non-Hispanic White youth.Conclusion: For American youth, race/ethnicity limits the health gains that are expected to follow parental educational attainment. While high parental educational attainment is protective against smoking overall, non-Hispanic Whites (the most socially privileged group) gain most and Blacks and Hispanics (the least socially privileged groups) gain least from such resource. In addition to addressing low SES, researchers and policymakers should identify and address mechanisms by which high SES minority youth remain at risk of tobacco use.Keywords: education, smoking, tobacco use, population groups, ethnicity, socioeconomic position, socioeconomic status, youth, adolescents